Sales Performance Analysis in Adding New Indihome Customers (Case Study in Telkom Jember Area) - Evi Nur Cahyanti; Kurniawati; Shine Pintor Siolemba Patiro (PT FORMOSA CENDEKIA GLOBAL, 2024)
Sales Force is an important part of PT Telkom Indonesia's position which has a role in making the company successful. Sales Force finds it difficult to make offers to get customers. Sales Forces do not get a fixed salary, they only get a fee based on new customer orders whose been activated on the same day, so this makes Sales Force less motivated to work. It is suspected that there is miss preception between the Sales Force and the Organization which can influence their job satisfaction and performance. This research presents the results of descriptive statistical analysis, validity and reliability tests of measurement model parameters, as well as the results of testing the research structural model. The descriptive statistical analysis, validity test and reliability test in this research were analyzed using SMARTPLS software. Meanwhile, hypothesis testing and model suitability analysis in this research were carried out using the variance-based Structural Equation Modeling (SEM) method. Data collection was carried out directly by distributing questionnaires to 101 respondents, who were in the IndiHome Sales area for the period 2019 – July 2023. For the result analysis, Work Motivation and Self Efficacy have positive significant for Sales Force Job Satisfaction. Work motivation and Climate Organization have a positive significant effect on Sales Force Job Performance. Climate Organization does not have a significant effect on job satisfaction. Self-Efficacy does not have a significant effect on Performance. Job Satisfaction does not have a significant effect on Sales Performance.